The Impact of Hate Comments on Social Media Users' Self-Confidence: An Analysis Grounded in Social Comparison Theory and Cyberbullying Research - Ismail, Lukman; Mukramin, Sam’un; Fatmawati, Fatmawati; Nursida, Andi (Acta Psychologia, 2024)
This study investigates the relationship between hate comments on social media and users' self-confidence, providing a comprehensive analysis grounded in Social Comparison Theory and cyberbullying research. Using a mixed-methods approach, the study surveys a diverse sample of social media users and conducts in-depth interviews to explore the extent and impact of exposure to hate comments. The findings reveal a significant negative correlation between the frequency of hate comments and self-confidence levels, with younger users and women being particularly vulnerable. The study also identifies the moderating role of social support, where strong support networks help mitigate the negative effects of hate comments. Potential limitations include sample size constraints, self-report biases, and challenges in generalizability. The implications of the findings are far-reaching, suggesting the need for individual strategies to manage social media use, therapeutic interventions by mental health professionals, and enhanced anti-harassment measures by social media platforms. By addressing these issues, we can foster a healthier digital environment that supports users' mental health and well-being.